From deportations to “frozen conflicts”: Russian nationalism, ethnic engineering and violence in the Soviet and post-Soviet space - Marsili, M. (Frontiers in Political Science, 2026)
This article examines how Soviet and post-Soviet forms of Russian nationalism used ethnic engineering – above all mass deportations and demographic reshuffling – to transform ethno-national diversity into a structural source of conflict. Building on a qualitative, historical-comparative design, the study combines close reading of Soviet constitutional and legal texts with secondary literature on deportations and “frozen conflicts” to trace mechanisms linking Stalin-era policies to contemporary wars in the post-Soviet space. Archival decrees, census data and administrative cartography are analysed through thematic coding (e.g., “collective punishment,” “demographic engineering,” “border manipulation”) and compared across key episodes such as the deportation of Chechens and Ingush, Crimean Tatars and Volga Germans. The article then connects these historical patterns to post-1991 conflicts in the Caucasus, Crimea/Donbas and Central Asia, showing how earlier deportations and territorial rearrangements created asymmetric republics, competing memories of victimhood and territorially embedded grievances. Rather than treating Russian nationalism as a purely ideological phenomenon, the analysis conceptualizes it as a repertoire of state practices that combine coercive removal, selective rehabilitation and later “protection” of co-nationals abroad. The findings challenge accounts that explain post-Soviet conflicts solely through democratization failure or great-power rivalry, arguing instead that ethnic wars in the region are rooted in a long genealogy of state-led population politics. The article concludes by discussing the broader implications for theories of ethnofederalism and for contemporary debates on how authoritarian regimes manage diversity through forced mobility rather than inclusive citizenship.